Problems in The Implementation of Sharia Audit in Indonesia: A Systematic Literature Review using PRISMA - Al Rieza, Irfaul Risqoh; Taqiyya, Arinan Hananan (Accounting and Sustainability, 2023)
This research aims to find out the problems encountered in the practice of sharia auditing to be recommended to stakeholders in order to get solutions and find solutions. The method used is qualitative with a literature study approach. Data analysis tools with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) technique. This research uses secondary data taken from the Publish or Perish software on the Google Scholar database. The results showed that there were 41 papers that became the population, then filtered and produced 17 final articles which became the main data source in the study. Of the 17 articles processed, all of them are problems encountered by Islamic audit practitioners encountered in the field.  It was found that there are five basic problems in Islamic auditing that can be a reference for the relevant stakeholders to solve in order to improve the performance of Islamic auditing. The five problems are (1) Sharia audit regulations that have not been accommodated nationally, (2) Availability and competence of Human Resources as sharia auditors that are not optimal, (3) Management of the sharia audit process that is not effective and efficient, and (4) The practice of the sharia audit process still focuses on operational audits rather than audits of sharia aspects, (5) Unclear scope of sharia audits.